A super-early-strength and super-high-performance potassium magnesium phosphate cement-based composite material and a preparation method thereof
By using materials such as refired magnesium oxide and potassium dihydrogen phosphate, combined with high-efficiency composite retarder and water reducing agent, ultra-premature strength and ultra-high performance potassium phosphate magnesium cement-based composite materials are prepared, which solves the problem of limited strength development of existing ultra-high performance concrete in the ultra-premature age period, and achieves excellent mechanical properties and environmental friendliness.
Patent Information
- Application Number
- CN202411803193.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-12-10
AI Technical Summary
Existing ultra-high performance concrete has limited strength development during the ultra-early age period (especially within a few hours) and cannot meet the civil engineering needs that have high requirements for early strength.
Recalcined magnesium oxide and potassium dihydrogen phosphate are used as the main cement raw materials, combined with auxiliary cementitious materials such as fume, wollastonite powder, metakaolin and fly ash, and use high-efficiency composite retarder and water reducing agent to achieve the preparation of ultra-premature and ultra-high performance potassium magnesium phosphate cement-based composite materials under ultra-low water cement ratio.
The compressive strength of the ultra-early age (such as within 3 hours) reaches 92 MPa, the direct tensile strength reaches 10 MPa, and the flexural strength reaches 37 MPa, meeting the civil engineering needs with high requirements for hourly strength, and it does not require special maintenance and is environmentally friendly.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of preparation and application of magnesium phosphate cement-based materials, and in particular to an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof. Background Art
[0002] Some in-service civil engineering facilities have become aged and damaged, and are in urgent need of maintenance and reinforcement. At the same time, the construction of various civil engineering projects, such as super-high-rise buildings, large-span bridges, undersea tunnels, marine engineering, underground disposal repositories, etc., is also emerging. The maintenance and reinforcement of in-service aging civil engineering facilities and the construction of civil engineering projects have put forward high requirements on the environmental friendliness and comprehensive performance of modern concrete materials. Ultrahigh performance concrete (UHPC) is a cement-based material. Compared with traditional cement-based materials, it has the advantages of significantly higher strength, higher toughness and excellent durability. Therefore, ultrahigh performance concrete is being actively promoted and applied in various civil engineering projects, and its application prospects are good. At present, the preparation of ultra-high performance concrete uses silicate cement as the main cementitious raw material, so its strength development at early age, especially at ultra-early age (within a few hours of hydration), is limited, and autoclaving is required to accelerate strength development. Therefore, this type of ultra-high performance concrete cannot well meet the needs of civil engineering projects with high requirements for early (especially ultra-early age) strength, such as emergency repair and construction of damaged infrastructure (highways, airport runways, etc.), marine concrete projects, special projects, etc., as well as emergency and safe consolidation of nuclear waste in the field of nuclear waste safety. It can be seen that there is a practical engineering demand for the invention of ultra-early strength ultra-high performance cement-based materials (concrete) to replace traditional ultra-high performance concrete for applications such as the above-mentioned projects with high requirements for early (especially ultra-early age) strength of materials.
[0003] Chinese patent application CN110803906B discloses an ultra-high performance repair concrete prepared with a sulphoaluminate cement-portland cement composite cementitious system, whose 3-hour maximum compressive and flexural strengths are 45 MPa and 15 MPa, respectively; Chinese patent application CN115784647B discloses an early-strength ultra-high performance concrete prepared with sulphoaluminate cement, whose 2-hour compressive strength is 66 MPa. Chinese patent application CN116813283A discloses a high-flexural ultra-early-strength ultra-high performance concrete with an initial setting time greater than 30 min, whose 3-hour compressive and flexural strengths are 37 MPa and 14 MPa, respectively; Chinese patent application CN115819052 A discloses an ultra-early-strength ultra-high performance concrete, whose 6-hour maximum compressive and flexural strengths are 25 MPa and 6 MPa, respectively. The above-mentioned public patents achieve the improvement of the mechanical properties of cement-based materials at ultra-early ages (2 to 6 h) by modifying sulphoaluminate cement or compounding sulphoaluminate cement with silicate cement, but the improvement effect is still relatively limited; in addition, tensile strength is one of the important properties of ultra-high performance concrete. However, the above-mentioned public patent materials have not published the tensile strength values of the corresponding materials. Generally speaking, the tensile strength of concrete is much lower than its compressive strength, and there are clear strength requirements for the tensile strength of UHPC in relevant specifications such as T / CECS 10107-2020 "Technical Requirements for Ultra-High Performance Concrete (UHPC)".
[0004] Magnesium phosphate cement is a special cementitious material. According to the different raw materials phosphate used, it can be subdivided into ammonium magnesium phosphate cement, potassium magnesium phosphate cement, sodium magnesium phosphate cement, etc. It usually has the advantages of fast setting and hardening, high early strength, high bonding strength with the old concrete matrix, good volume stability, and good solidification ability for heavy metals and active metals. Magnesium phosphate cement-based materials are usually used for the maintenance / reinforcement or emergency repair and construction of airport runways, highways, bridges, cold region construction projects, marine concrete projects, and certain projects; in addition, magnesium phosphate cement-based materials can also be used for the solidification and safe disposal of nuclear waste. The preparation of ultra-high performance magnesium phosphate cement-based materials (concrete) using magnesium phosphate cement as the main cementitious raw material can overcome the weakness of the slow early strength development of traditional silicate cement ultra-high performance concrete, and at the same time has the advantages of normal construction at low temperatures and strong resistance to salt erosion. In the literature [1] "Preparation and Performance Study of Ultra-High Performance Magnesium Phosphate Cement Bridge Deck Pavement Materials", a super-high performance magnesium ammonium phosphate cement-based material was prepared using dead-burned magnesium oxide and ammonium dihydrogen phosphate as raw materials. Its 6-hour maximum compressive and flexural strengths were 82 MPa and 18 MPa, respectively. Although the early mechanical properties of this material are close to the 28-day mechanical properties requirements of traditional silicate cement ultra-high performance concrete (RPC100 grade), its setting time is only 15 minutes, which makes actual construction operation difficult. In addition, this ultra-high performance cement-based material uses magnesium ammonium phosphate cement as the main cementing material, so ammonia release is inevitable during the preparation and application of this material, which has adverse effects on both humans and the environment. Potassium magnesium phosphate cement uses potassium dihydrogen phosphate as the reaction phosphate, and has similar mechanical properties to magnesium ammonium phosphate cement, but avoids the disadvantage of magnesium ammonium phosphate cement releasing ammonia during use, making it more environmentally friendly. However, there is currently no relevant public information on the preparation of ultra-high performance cement-based composites using potassium magnesium phosphate cement as the main cementing material.
[0005] The invention of ultra-high performance potassium magnesium phosphate cement-based composite materials has the following key difficulties: i) Traditional borate retarders cannot effectively delay the setting time of potassium magnesium phosphate cement-based materials at ultra-low water-cement ratios (w / b), resulting in rapid setting of the materials within a few minutes and too short an operation time; ii) Potassium magnesium phosphate cement-based materials have extremely poor fluidity at ultra-low w / b, making them difficult to mix and unable to achieve the tightest packing of solid particles. How to solve the above key difficulties and achieve the research and development and preparation of ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite materials so that they can be applied to different fields and meet different application requirements, especially for maintenance / reinforcement, emergency repairs, and emergency construction in the above-mentioned civil engineering fields, as well as the solidification of heavy metals and active metals in the environmental field and the safe disposal of (nuclear) waste, is an urgent problem to be solved. Summary of the invention
[0006] The purpose of the present invention is to provide an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof in order to solve the above problems. The ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material of the present invention uses heavy burned (or dead burned) magnesium oxide and potassium dihydrogen phosphate as cement raw materials, silica fume, wollastonite powder, metakaolin and fly ash as auxiliary cementitious materials, quartz sand as aggregate, and adopts high-efficiency composite retarder and water reducer to realize the preparation and application of UHPMKPCC under ultra-low water-cement ratio.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] The first object of the present invention is to provide an ultra-early-strength ultra-high-performance magnesium potassium phosphate cement-based composite material (UHPMKPCC), wherein the content of each component material in the ultra-early-strength ultra-high-performance magnesium potassium phosphate cement-based composite material (concrete) is as follows:
[0009] Dead-burned magnesium oxide 767.6~900 kg / m 3 ;
[0010] Potassium dihydrogen phosphate 300~432.0 kg / m 3 ;
[0011] Silica fume 151~302 kg / m 3 ;
[0012] Auxiliary cementitious materials 0~200kg / m 3 ;
[0013] Sodium dihydrogen phosphate 0~100 kg / m 3 ;
[0014] Quartz sand 400~1000 kg / m 3 ;
[0015] Composite retarder 13.2~26.4 kg / m 3 ;
[0016] Water reducing agent 0.7~7 kg / m 3 ;
[0017] Fiber 100~240 kg / m 3 ;
[0018] Water 180~226 kg / m 3 .
[0019] More preferably, the ratio of water to potassium dihydrogen phosphate is 0.5 to 0.66.
[0020] More preferably, the magnesium-to-phosphorus molar ratio (Mg / PO4) of the magnesium in the dead-burned magnesium oxide to the phosphorus in potassium dihydrogen phosphate is 6-10.
[0021] Further preferably, the average particle size of the dead-burned magnesium oxide is 20-60 μm, and the dead-burned magnesium oxide includes MgO, and the MgO content is ≥80%.
[0022] More preferably, the potassium dihydrogen phosphate has an average particle size of 50 to 300 μm and a purity of ≥90%.
[0023] Further preferably, the average particle size of the silica fume is 0.1-0.3 μm, and the silica fume includes SiO2, and the SiO2 content is ≥90%.
[0024] Furthermore, the auxiliary cementitious material is selected from one or more of fly ash, wollastonite powder, metakaolin and the like.
[0025] Further preferably, when the auxiliary cementitious material is fly ash, the dosage per cubic meter is 0-200 kg / m 3 .
[0026] Further preferably, when the auxiliary gelling material is wollastonite powder, the dosage per cubic meter is 0-150 kg / m 3 .
[0027] More preferably, when the auxiliary cementitious material is metakaolin, the dosage is 0-150 kg / m 3 .
[0028] Further preferably, the fly ash is one or more combinations of Class F or Class C fly ash (including Class I, Class II, Class III, and ultrafine fly ash).
[0029] More preferably, the average particle size of the wollastonite powder is 10-23 μm.
[0030] More preferably, the average particle size of the metakaolin is 2 to 10 μm.
[0031] Furthermore, the sodium dihydrogen phosphate is used as a phosphate that can replace part of the potassium dihydrogen phosphate.
[0032] Further preferably, the sodium dihydrogen phosphate replaces 0-15% of potassium dihydrogen phosphate based on the single dosage ratio.
[0033] More preferably, the sodium dihydrogen phosphate has an average particle size of 50 to 600 μm and a purity of ≥90%.
[0034] More preferably, the quartz sand has a particle size of 0.16 to 1.25 mm.
[0035] Furthermore, the composite retarder is a mixture of zinc acetate and borate.
[0036] Furthermore, in the composite retarder, the mass ratio of zinc acetate to borate is 1:9 to 9:1.
[0037] Further preferably, in the composite retarder, the mass ratio of zinc acetate to borate is 1:3, 1:1, 3:1.
[0038] Further preferably, the zinc acetate is zinc acetate dihydrate, in the form of white crystals, with a purity of ≥ 99%.
[0039] Further preferably, the borate is one or more of boric acid or sodium borate, in the form of white powder with a purity of ≥99%.
[0040] Furthermore, the preparation method of the composite retarder is selected from one or more of the following methods:
[0041] Method 1: dissolving the composite retarder in mixing water and then mixing to prepare UHPMKPCC;
[0042] Method 2: Dissolve zinc acetate in the composite retarder in mixing water, add borate into the solid mixture, and then mix to prepare UHPMKPCC;
[0043] Method 3: The composite retarder is added into the solid mixture, and then water is added to mix to prepare UHPMKPCC.
[0044] The solid mixture includes one or more of dead-burned magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, silica fume, auxiliary cementitious materials, quartz sand, and water reducing agent.
[0045] Further preferably, the fiber includes steel fiber or a composite fiber including steel fiber and non-metallic fiber, the steel fiber is a fine steel fiber, the steel fiber diameter is 0.1-0.22 mm, the steel fiber length is 6-20 mm, the steel fiber includes one or more of copper-plated steel fiber, stainless steel fiber, and ordinary carbon steel fiber; the non-metallic fiber includes one or more of POM fiber, PE fiber, PVA fiber, and PP fiber, the steel fiber can be used alone, and the non-metallic fiber can be used in combination with the steel fiber.
[0046] Furthermore, the water reducer is one or more combinations of naphthalene-based water reducers, aminosulfonate-based water reducers, and lignin sulfonate-based water reducers.
[0047] Furthermore, the water may be tap water.
[0048] The second object of the present invention is to provide a method for preparing an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material, comprising but not limited to the following steps:
[0049] Mix water, dead-burned magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, silica fume, auxiliary cementitious material, quartz sand, water reducing agent, and composite retarder, stir until slurry is formed, then add steel fiber and stir rapidly to evenly disperse the steel fiber in the slurry to obtain a mixture;
[0050] The prepared mixture is formed in a mold or directly applied to actual engineering, and after solidification and hardening, an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material is formed.
[0051] Optionally, the preparation method comprises the following steps:
[0052] 1) dry-mixing the dead-burned (or dead-burned) magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, auxiliary cementitious materials such as one or more of silica fume, fly ash, wollastonite powder, metakaolin, etc., and quartz sand in a mixer;
[0053] 2) Add the composite retarder, water reducing agent and mixing water to the dry mix and stir until a slurry is formed, then add the fiber and stir quickly to evenly disperse the fiber in the slurry to obtain a mixture;
[0054] 3) The prepared mixture is molded into a mold or directly applied to actual engineering, and after solidification and hardening, an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material is formed.
[0055] Optionally, the preparation method comprises the following steps:
[0056] 1) Add zinc acetate in the composite retarder into the mixing water to dissolve it and form a zinc acetate solution;
[0057] 2) Evenly dry-mix borate, dead-burned magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, water reducing agent, silica fume, other auxiliary cementitious materials such as fly ash, wollastonite powder, metakaolin, etc., and quartz sand in a mixer to obtain a dry mix;
[0058] 3) Adding the zinc acetate solution to the dry mix and stirring rapidly to form a slurry, then adding the fiber to the slurry and stirring rapidly until the fiber and the slurry are evenly mixed to obtain a mixed material;
[0059] 4) The prepared mixture is molded into a mold or directly applied to actual engineering, and after solidification and hardening, an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material is formed.
[0060] Optionally, the preparation method comprises the following steps:
[0061] 1) Add all the composite retarder into the mixing water to dissolve it to form a mixed solution of borate and zinc acetate;
[0062] 2) Evenly dry-mix dead-burned magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, water reducing agent, silica fume, other auxiliary cementitious materials such as fly ash, wollastonite powder, metakaolin, etc., and quartz sand in a mixer to obtain a dry mix;
[0063] 3) Add the composite retarder solution to the dry mix and quickly stir it into a slurry, then add the fiber to the slurry and quickly stir it until the fiber and the slurry are evenly mixed to obtain a mixed material;
[0064] 4) The prepared mixture is molded into a mold or directly applied to actual engineering, and after solidification and hardening, an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material is formed.
[0065] Optionally, the preparation method comprises the following steps:
[0066] 1) Evenly mix dead-burned magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, water reducing agent, silica fume, other auxiliary cementitious materials such as fly ash, wollastonite powder, metakaolin, etc., and quartz sand in a mixer to obtain a solid mixture, add the composite retarder into the solid mixture, and mix to obtain a retarder mixture;
[0067] 2) Add water to the retarder mixture and stir to form a slurry, then add the fiber to the slurry and stir rapidly until the fiber and the slurry are evenly mixed to obtain a mixture;
[0068] 3) The prepared mixture is molded into a mold or directly applied to actual engineering, and after solidification and hardening, an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material is formed.
[0069] The principle of the present invention is:
[0070] 1) The present invention determines the optimal ranges of two key parameters, namely, the ratio of water to potassium dihydrogen phosphate (w / p) and the magnesium-phosphorus molar ratio (Mg / PO4), based on the basic theory of hydration reaction of potassium magnesium phosphate cement, and obtains that when w / p is in the range of 0.53-0.66 and the Mg / PO4 molar ratio is in the range of 7-8, a potassium magnesium phosphate cement matrix with good fluidity, low drying shrinkage and high mechanical strength can be obtained; in addition, the high-efficiency composite retarder used in the present invention can effectively regulate the setting time of potassium magnesium phosphate cement under ultra-low water-binder ratio (w / b), effectively solving the problem that traditional borates cannot effectively retard the setting and the setting time is too short to be prepared.
[0071] 2) Different from the traditional method of introducing fly ash to improve fluidity, the present invention uses silica fume as the main component of cementitious materials to improve the fluidity of steel fiber reinforced potassium magnesium phosphate cement-based materials at ultra-low water-binder ratio (w / b), which is mainly due to the "ball effect" of a huge number of nano-spherical silica fume particles. Under the premise that the setting time and fluidity of fiber-reinforced potassium magnesium phosphate cement-based materials at ultra-low water-binder ratio (w / b) are guaranteed, the present invention adopts the most dense packing model, selects other auxiliary cementitious materials with different particle size ranges and different activities such as wollastonite powder, metakaolin, fly ash, etc., and compounds with silica fume, potassium magnesium phosphate cement and steel fiber, so as to achieve the most dense packing between the components, and further optimize and improve the microstructure and mechanical properties of the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material of the present invention.
[0072] In addition, for the preparation of UHPC with ordinary Portland cement, the addition of silica fume will increase the viscosity of concrete, thereby significantly reducing the fluidity of Portland cement, so it is necessary to increase the amount of high-efficiency water reducer. However, for the present invention, the addition of silica fume can effectively reduce the water content of magnesium phosphate cement and improve the mechanical properties.
[0073] Compared with the prior art, the present invention has the following advantages:
[0074] 1) The ultra-early-strength and ultra-high-performance potassium magnesium phosphate cement-based composite material of the present invention can reach a 3-hour compressive strength of 92 MPa, a direct tensile strength of 10 MPa, a flexural strength of 37 MPa, and a 1-day compressive strength of 108 MPa. It has significant ultra-early-strength characteristics and meets the above-mentioned various engineering requirements, especially special engineering requirements such as emergency repair and emergency construction that have high requirements for hourly strength. The 3-hour flexural strength of the material of the present invention exceeds the 28-day flexural strength requirement of RPC180 grade (GB / T 31387-2015) (i.e., 24 MPa); the 3-hour direct tensile strength exceeds the highest tensile strength grade requirement of UT4 (T / CECS 10107-2020) (i.e., ≥10 MPa); the 1-day compressive strength exceeds the 28-day compressive strength requirement of RP100 grade (GB / T 31387-2015) (i.e., ≥100 MPa);
[0075] 2) The high-efficiency composite retarder used in the present invention effectively prolongs the setting time of potassium magnesium phosphate cement-based materials at ultra-low water-cement ratio (w / b), solving the problem that the traditional borate has limited retarding effect and the setting time is too short to be prepared. For example, at w / b = 0.15, adding 8% (mass percentage of potassium magnesium phosphate cement) of boric acid can only prolong the retarding time to 16 min, while adding only 1.2% of the high-efficiency composite retarder can effectively prolong the setting time to 35 min, ensuring the progress of the construction (preparation) operation;
[0076] 3) The ultra-early-strength ultra-high-performance potassium magnesium phosphate cement-based composite material of the present invention has good volume stability and has a significantly lower drying shrinkage rate compared with ultra-high-performance concrete made of silicate cement. For example, the 60-day drying shrinkage rate of the material is only 0.14‰. In addition, unlike ultra-high-performance concrete made of silicate cement, which requires steam curing to improve early strength, the ultra-early-strength ultra-high-performance potassium magnesium phosphate cement-based composite material of the present invention does not require special curing, and can achieve rapid development of mechanical strength through air curing at room temperature. Compared with the ultra-high-performance ammonium magnesium phosphate cement-based materials reported previously, the ultra-early-strength ultra-high-performance potassium magnesium phosphate cement-based composite material of the present invention does not release ammonia during preparation and service, and is environmentally friendly. DETAILED DESCRIPTION
[0077] The present invention is described in detail below in conjunction with specific embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, several variations and improvements may be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0078] The invention discloses an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof. The outstanding characteristics of the material are that its ultra-early age (such as within 3 hours) compressive strength is close to the 28-day compressive strength requirement of RPC100 grade concrete, and its ultra-early age (such as within 3 hours) direct tensile strength and flexural strength are higher than the 28-day related strength requirements of UT4 and RPC180 grade concrete, and its setting time can be effectively regulated to meet different engineering requirements. The ultra-early-strength ultra-high-performance magnesium potassium phosphate cement-based composite material (concrete, Ultrahigh performance magnesium potassium phosphate cement-based composites, UHPMKPCC) uses dead-burned magnesium oxide and potassium dihydrogen phosphate (sodium dihydrogen phosphate can be selected to replace a small part of potassium dihydrogen phosphate to enrich the hydrate phase and optimize the microstructure) as cement raw materials, uses silica fume as one of the cementitious materials, uses wollastonite powder, metakaolin and fly ash as auxiliary cementitious materials, uses quartz sand as aggregate, and adopts a high-efficiency composite retarder and a water reducer to achieve the preparation and application of UHPMKPCC under ultra-low water-cement ratio. Compared with the existing ultra-high performance silicate cement-based materials (concrete, UHPC) technology, the UHPMKPCC of the present invention has excellent mechanical properties at an ultra-early age (within 3 hours, the compressive strength can exceed 90 MPa, the flexural strength and tensile strength exceed 35 MPa and 10 MPa respectively), and has the advantages of low drying shrinkage (significantly lower drying shrinkage); compared with the existing ultra-high performance magnesium ammonium phosphate cement-based materials technology reported, the UHPMKPCC of the present invention has the advantages of effective control of setting time and no ammonia release. The UHPMKPCC of the present invention can be applied to different projects in different fields, including but not limited to the following: maintenance, reinforcement, emergency repair, emergency construction, etc. of civil buildings, roads, bridges, tunnels, marine concrete engineering and engineering in the field of civil engineering, safe solidification and disposal of radioactive nuclear waste in the field of safe disposal of nuclear waste, and related uses in other fields.
[0079] Any features such as preparation methods, materials, structures or composition ratios that are not clearly described in this technical solution shall be deemed as common technical features disclosed in the prior art.
[0080] In the following examples of the present invention, all raw materials are commercially available.
[0081] The following examples and comparative examples mainly include the determination of the setting time, compressive strength, flexural strength and direct tensile strength of the ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material, respectively referring to JGJ / T70-2009 "Standard for Test Methods for Basic Properties of Building Mortar", GB / T17671-1999 "Test Method for Strength of Cement Mortar" and T / CECS 10107-2020 "Technical Requirements for Ultra-High Performance Concrete (UHPC)".
[0082] The dead-burned magnesia was purchased from Jinan Ludong Refractory Co., Ltd., with an average particle size of 26.2 μm and a MgO content of ≥ 95.4%;
[0083] Potassium dihydrogen phosphate (KH2PO4) was industrial-grade potassium dihydrogen phosphate purchased from Hubei Qianding Technology Co., Ltd., with an average particle size of 85 μm and a purity of ≥ 99%;
[0084] The silica fume was purchased from Shanghai Tiankai Building Materials Technology Co., Ltd., with an average particle size of 0.29 μm and a SiO2 content of ≥98%;
[0085] The fly ash used was ultrafine fly ash purchased from Lingshou County Shengfeng Mineral Products Processing Plant, with an average particle size of 8.61 μm;
[0086] Wollastonite powder was purchased from Lishu Dadingshan Wollastonite Co., Ltd. in Jilin Province, with an average particle size of 11.5 μm;
[0087] The metakaolin was purchased from Inner Mongolia Chaopai New Materials Co., Ltd., with an average particle size of 3 μm;
[0088] The quartz sand is purchased from Heyuan Wanchuan Quartz Development Co., Ltd., with a particle size of 40-70 mesh;
[0089] The fibers were purchased from Ganzhou Daye Metal Fiber Co., Ltd.:
[0090] Copper-plated fine straight steel fiber, length 10 mm, diameter 0.12 mm;
[0091] Stainless steel fine straight steel fiber, length 14 mm, diameter 0.16 mm;
[0092] and POM fibers purchased from Chongqing Yuntianhua Tianju New Materials Co., Ltd., with a length of 12 mm and a diameter of 0.1 mm;
[0093] The water reducer is a naphthalene water reducer purchased from Shanghai Chenqi Chemical Technology Co., Ltd., which is in the form of brown-yellow powder;
[0094] The composite retarder is the composite retarder No. 2 used in Example 2 of "CN117447115A A composite retarder and its application in magnesium phosphate cement-based materials", and the method 2 of using the retarder is used as the method of using the retarder of the present invention. The selected composite retarder is composed of zinc acetate dihydrate and boric acid in a 1:1 (mass ratio). Zinc acetate dihydrate and boric acid reagent are purchased from Shanghai MacLean Biochemical Technology Co., Ltd.:
[0095] Zinc acetate dihydrate, white crystals, purity ≥99%;
[0096] Boric acid, white powder, purity ≥99.5%.
[0097] Since zinc acetate dihydrate contains 16.4 wt% of water, it is taken into account when calculating the material mix ratio to accurately calculate the amount of water used in material preparation.
[0098] Embodiment 1:
[0099] Example 1 provides an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof. The specific steps of the preparation method are as follows:
[0100] 1) Weigh the raw materials of each component according to the mix ratio shown in Table 1;
[0101] 2) Add zinc acetate dihydrate into the mixing water to dissolve and form a zinc acetate solution;
[0102] 3) slowly and evenly dry-mixing the boric acid, the dead-burned magnesium oxide, potassium dihydrogen phosphate, naphthalene-based water reducer, silica fume, other auxiliary cementitious materials (such as fly ash, wollastonite powder, metakaolin, etc.), and quartz sand in a mixer at a stirring rate of 62 rpm for 2 min to obtain a dry mix;
[0103] 4) Add the zinc acetate solution to the dry mix and stir rapidly to form a slurry at a rate of 125 rpm for 2 to 3 min, then add the fiber to the slurry and stir rapidly until the fiber and the slurry are evenly mixed to obtain a freshly mixed material;
[0104] 5) The newly mixed material is molded, vibrated, and smoothed until the surface is smooth and uniform, and cured at room temperature to finally obtain the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material.
[0105] Example 1 adopts Mg / PO4 molar ratio = 7, w / b = 0.15, silica fume content (based on the mass of total cementitious materials (gel materials include dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and wollastonite powder)) is 15%, other auxiliary cementitious materials are selected from wollastonite powder, the content of which is 5% (based on the mass of total cementitious materials), the content of composite retarder is 1% (based on the mass of potassium magnesium phosphate cement), the content of naphthalene-based water reducer is 0.5‰ (based on the mass of total cementitious materials), the sand-cement ratio is 0.4 (the ratio of quartz sand to the mass of total cementitious materials), and the fiber is selected from copper-plated fine steel fiber (diameter 0.12 mm, length 10 mm), and the volume content is 2% (based on the total volume of mortar). The auxiliary cementitious materials (i.e. silica fume and wollastonite powder) used in this material can play the following synergistic role: silica fume can effectively improve the fluidity of the slurry and dense the matrix, while wollastonite powder plays the role of mineral microfiber, enhancing the toughness of the matrix and significantly improving the tensile strength and flexural strength of the material.
[0106] Embodiment 2:
[0107] Example 2 provides an ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof, and the specific preparation steps are the same as those of Example 1. As shown in the proportions in Table 1, the Mg / PO4 molar ratio used is 7, w / b = 0.15, the silica fume content (based on the total cementitious material (gel material includes dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and metakaolin)) is 15%, other auxiliary cementitious materials are selected from metakaolin, the content is 5% (based on the total cementitious material mass), the composite retarder content is 1% (based on the potassium magnesium phosphate cement mass), the naphthalene water reducer content is 0.5‰ (based on the total cementitious material mass), the sand-binder ratio is 0.4 (the ratio of quartz sand to the total cementitious material mass), the fiber is selected as copper-plated fine steel fiber (diameter 0.12 mm, length 10 mm), the volume content is 2% (based on the total volume of mortar), and the specific material composition ratio is shown in Table 1. The auxiliary cementitious materials (i.e. silica fume and kaolin) used in this material can play the following synergistic role: silica fume can effectively improve the fluidity of the slurry and compact the matrix, while kaolin can enhance the mechanical properties and improve the durability.
[0108] Embodiment 3:
[0109] Example 3 provides an ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof, and the specific preparation steps are the same as those of Example 1. As shown in the proportions in Table 1, the Mg / PO4 molar ratio = 8, w / b = 0.14, the silica fume content is 10% (based on the total cementitious material (gel material includes dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and ultrafine fly ash)), other auxiliary cementitious materials are ultrafine fly ash, the content is 10% (based on the total cementitious material mass), the composite retarder content is 1% (based on the mass of potassium magnesium phosphate cement), the naphthalene water reducer content is 0.5‰ (based on the total cementitious material mass), the sand-binder ratio is 0.4 (the ratio of quartz sand to the total cementitious material mass), the fiber is selected as copper-plated fine steel fiber (diameter 0.12 mm, length 10 mm), the volume content is 2% (based on the total volume of mortar), and the specific material composition ratio is shown in Table 1. The auxiliary cementitious materials (i.e. silica fume and ultrafine fly ash) used in this material can play the following synergistic role: the nano-spherical particles of silica fume and the micron-spherical particles of ultrafine fly ash play a "ball effect" at different scales, synergistically improving the fluidity of the slurry, and densifying the matrix at different scales, thereby improving mechanical properties and durability.
[0110] Embodiment 4:
[0111] Example 4 provides an ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof, and the specific preparation steps are the same as those of Example 1. As shown in Table 1, the Mg / PO4 molar ratio = 7, w / b = 0.15, the silica fume content is 15% (based on the mass of the total cementitious material (gel material includes dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and wollastonite powder)), other auxiliary cementitious materials are selected from wollastonite powder, the content is 5% (based on the mass of the total cementitious material), the content of the composite retarder is 1.2% (based on the mass of potassium magnesium phosphate cement), the content of the naphthalene-based water reducer is 0.5‰ (based on the mass of the total cementitious material), and the fiber is selected from copper-plated fine steel fiber (diameter 0.12 mm, length 10 mm), and the volume content is 2% (based on the total volume of the mortar).
[0112] Embodiment 5:
[0113] Example 5 provides an ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof, and the specific preparation steps are the same as those in Example 1. The Mg / PO4 molar ratio used is 7, w / b = 0.15, the silica fume content is 20% (based on the mass of the total cementitious material (the gel material includes dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and ultrafine fly ash)), no other auxiliary cementitious materials are used, the composite retarder content is 1% (based on the mass of potassium magnesium phosphate cement), the naphthalene-based water reducer content is 0.5‰ (based on the mass of the total cementitious material), the sand-binder ratio is 0.4 (the ratio of quartz sand to the mass of the total cementitious material), the fiber selection is copper-plated fine steel fiber (diameter 0.12 mm, length 10 mm), the volume content is 2% (based on the total volume of mortar), and the specific material composition ratio is shown in Table 1. The purpose of setting up this embodiment is mainly to show that the present invention can still prepare an ultra-high performance potassium magnesium phosphate cement-based composite material with ultra-early strength when only the main cementitious materials potassium magnesium phosphate cement and silica fume are used without using other auxiliary cementitious materials.
[0114] Embodiment 6:
[0115] Example 6 provides an ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof, and the specific preparation steps are the same as those of Example 1. As shown in Table 1, the molar ratio of Mg / PO4 is 7, w / b is 0.15, the amount of silica fume is 15% (based on the mass of the total cementitious material (gel material includes dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and wollastonite powder)), other auxiliary cementitious materials are selected from wollastonite powder, the amount of which is 5% (based on the mass of the total cementitious material), the amount of the composite retarder is 1% (based on the mass of potassium magnesium phosphate cement), the amount of the naphthalene-based water reducer is 0.5‰ (based on the mass of the total cementitious material), and the steel fiber is selected as stainless steel fine straight steel fiber (diameter 0.16 mm, length 14 mm to maintain the aspect ratio basically consistent with other embodiments), and the volume amount is 2% (based on the total volume of the mortar). The purpose of this embodiment is to prepare an ultra-early-strength, ultra-high-performance potassium magnesium phosphate cement-based composite material suitable for engineering environments with corrosive environments such as marine engineering and underground engineering, and stainless steel fibers are selected to prevent the steel fibers on the surface of the material from being corroded.
[0116] Embodiment 7:
[0117] Example 7 provides an ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof, and the specific preparation steps are the same as those of Example 1. As shown in Table 1, the molar ratio of Mg / PO4 is 7, w / b is 0.15, the amount of silica fume is 15% (based on the mass of the total cementitious material (gel material includes dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and wollastonite powder)), other auxiliary cementitious materials are selected from wollastonite powder, the amount of which is 5% (based on the mass of the total cementitious material), the amount of composite retarder is 1% (based on the mass of potassium magnesium phosphate cement), the amount of naphthalene-based water reducer is 0.5‰ (based on the mass of the total cementitious material), and the fiber selection is a composite of POM fiber (diameter 0.1 mm, length 12 mm) and copper-plated fine straight steel fiber (diameter 0.16 mm, length 14 mm), and the volume amount is 1% of POM fiber and 2% of copper-plated fine straight steel fiber (based on the total volume of mortar). The purpose of using POM fiber in this embodiment is to further improve the ductility of the material of the present invention and enhance the durability of the material.
[0118] Embodiment 8:
[0119] Example 8 provides an ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite material and a preparation method thereof, and the specific preparation steps are the same as those of Example 1. As shown in Table 1, the Mg / PO4 molar ratio is 7, sodium dihydrogen phosphate is used to replace 5% of potassium dihydrogen phosphate, w / b = 0.15, the silica fume content (based on the total cementitious material (gel material includes dead-burned magnesium oxide, potassium dihydrogen phosphate, silica fume, and wollastonite powder)) is 15%, other auxiliary cementitious materials are selected from wollastonite powder, the content is 5% (based on the total cementitious material mass), the composite retarder content is 1% (based on the mass of potassium magnesium phosphate cement), the naphthalene water reducer content is 0.5‰ (based on the total cementitious material mass), the sand-binder ratio is 0.4 (the ratio of quartz sand to the total cementitious material mass), and the fiber is selected as copper-plated fine steel fiber (diameter 0.12 mm, length 10 mm), and the volume content is 2% (based on the total volume of mortar).
[0120] Table 1 Proportion of the ultra-high performance potassium magnesium phosphate cement-based composite materials described in Examples 1 to 8 (kg / m 3 )
[0121]
[0122] In order to verify that the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material of the present invention has significant mechanical property advantages and that the preparation method of the present invention uses a composite auxiliary cementitious material with multiple gain effects, comparative examples 1 to 5 are set.
[0123] Comparative Example 1:
[0124] Comparative Example 1 provides a potassium magnesium phosphate cement-based composite material, and the preparation method of the potassium magnesium phosphate cement-based material is as follows:
[0125] 1) Weigh the raw materials of each component according to the mix ratio shown in Table 2;
[0126] 2) Add zinc acetate dihydrate into the mixing water to dissolve and form a zinc acetate solution;
[0127] 3) Evenly dry-mix dead-burned magnesium oxide, potassium dihydrogen phosphate, boric acid, naphthalene-based water reducer and quartz sand in a mixer at a stirring rate of 62 rpm for 2 min to obtain a dry mix;
[0128] 4) Add zinc acetate solution to the dry mix and stir rapidly to form a slurry at a rate of 125 rpm for 2 to 3 min, then add copper-plated fine steel fibers to the slurry and stir rapidly until the steel fibers and the slurry are evenly mixed to obtain a freshly mixed material;
[0129] 5) The newly mixed material is molded, vibrated, and smoothed until the surface is smooth and uniform, and cured at room temperature to obtain potassium magnesium phosphate cement-based material.
[0130] As shown in Table 2, the Mg / PO4 molar ratio used in Comparative Example 1 is 7, w / b = 0.2 (this water-binder ratio is selected to keep the fluidity of the fresh slurry basically the same as that of Comparative Examples 1-3), there is no auxiliary cementitious material, the amount of composite retarder is 1% (based on the mass of potassium magnesium phosphate cement), the amount of naphthalene-based water reducer is 0.5‰ (based on the mass of total cementitious material), the sand-binder ratio is 0.4 (the ratio of quartz sand to the mass of total cementitious material), and the volume amount of steel fiber is 2% (based on the total volume of mortar). The purpose of implementing this comparative example 1 is to verify the significant improvement of the fluidity and mechanical properties of the auxiliary cementitious material selected by the material of the present invention.
[0131] Comparative Example 2:
[0132] Comparative Example 2 provides a potassium magnesium phosphate cement-based composite material, and the specific preparation steps of the potassium magnesium phosphate cement-based material are the same as those of Comparative Example 1. As shown in Table 2, the Mg / PO4 molar ratio used in Comparative Example 2 is 4, w / b = 0.15, the silica fume content is 15% (based on the total cementitious material mass), the other auxiliary cementitious materials are wollastonite powder, the content is 5% (based on the total cementitious material mass), the content of the composite retarder is 1% (based on the potassium magnesium phosphate cement mass), the content of the naphthalene water reducer is 0.5‰ (based on the total cementitious material mass), the sand-binder ratio is 0.4 (the ratio of quartz sand to the total cementitious material mass), and the steel fiber volume content is 2% (based on the total volume of the mortar). Compared with Example 1, except for the different Mg / PO4 molar ratio, the other parameters of Comparative Example 2 are the same. The Mg / PO4 molar ratio of 4 is a commonly used value for potassium magnesium phosphate cement-based materials used in the field of civil engineering. The implementation of Comparative Example 2 is to verify the scientific rationality of the Mg / PO4 molar ratio range selected for the new material of the present invention.
[0133] Comparative Example 3:
[0134] Comparative Example 3 provides a potassium magnesium phosphate cement-based composite material, and the specific preparation steps of the potassium magnesium phosphate cement-based material are the same as those of Comparative Example 1. As shown in Table 2, the Mg / PO4 molar ratio used in Comparative Example 3 is 8, w / b = 0.165, the auxiliary cementitious material is selected as ultrafine fly ash with an amount of 20% (based on the total cementitious material mass), the composite retarder with an amount of 1% (based on the mass of potassium magnesium phosphate cement), the naphthalene water reducer with an amount of 0.5‰ (based on the mass of the total cementitious material), the sand-binder ratio is 0.4 (the ratio of quartz sand to the total cementitious material mass), and the steel fiber volume content is 2% (based on the total volume of the mortar). Compared with Example 3, Comparative Example 3 only selects ultrafine fly ash as an auxiliary cementitious material, and increases its dosage to 20%, and does not use silica fume. Since ultrafine fly ash can only reduce the water-binder ratio w / b to 0.165, it cannot be reduced to 0.14 to be consistent with Example 3, and can only keep the fluidity consistent with Example 3, and the other parameters are consistent. The implementation of Comparative Example 3 is to verify the effect of the new material of the present invention using silica fume as the basic cementitious material and combining it with ultrafine fly ash to improve the performance of potassium magnesium phosphate cement.
[0135] Comparative Example 4:
[0136] Comparative Example 4 provides a potassium magnesium phosphate cement-based composite material, and the specific preparation steps of the potassium magnesium phosphate cement-based material are the same as those of Comparative Example 1. As shown in Table 2, the Mg / PO4 molar ratio used in Comparative Example 4 is 7, w / b = 0.15, the silica fume content is 15% (based on the total cementitious material mass), the other auxiliary cementitious material is wollastonite powder, the content is 5% (based on the total cementitious material mass), the retarder uses boric acid and the content is 1% (based on the potassium magnesium phosphate cement mass), the naphthalene water reducer content is 0.5‰ (based on the total cementitious material mass), the sand-binder ratio is 0.4 (the ratio of quartz sand to the total cementitious material mass), and the steel fiber volume content is 2% (based on the total volume of mortar). Compared with Example 1, Comparative Example 4 replaces the composite retarder with boric acid and the content is kept consistent, and the other parameters are also kept consistent. The implementation of Comparative Example 4 is to verify the necessity of using a composite retarder in the new material of the present invention. Since the coagulation time of the comparative example using the same dosage of boric acid is too short and cannot even provide sufficient time for material preparation, only the coagulation time result of the comparative example is provided.
[0137] Comparative Example 5:
[0138] Comparative Example 5 provides a potassium magnesium phosphate cement-based composite material, and the specific preparation steps of the potassium magnesium phosphate cement-based material are the same as those of Comparative Example 1. As shown in Table 2, the Mg / PO4 molar ratio used in Comparative Example 5 is 7, w / b = 0.15, the silica fume content is 15% (based on the total cementitious material mass), the other auxiliary cementitious material is wollastonite powder, the content is 5% (based on the total cementitious material mass), the retarder uses zinc acetate and the content is 1% (based on the potassium magnesium phosphate cement mass), the naphthalene water reducer content is 0.5‰ (based on the total cementitious material mass), the sand-binder ratio is 0.4 (the ratio of quartz sand to the total cementitious material mass), and the steel fiber volume content is 2% (based on the total volume of mortar). Compared with Example 1, Comparative Example 5 replaces the composite retarder with zinc acetate and the content is kept consistent, and the other parameters are also kept consistent. The implementation of Comparative Example 5 is to verify the necessity of using a composite retarder in the new material of the present invention. Since the coagulation time of the comparative example using the same dosage of boric acid is too short and cannot even provide sufficient time for material preparation, only the coagulation time result of the comparative example is provided.
[0139] Table 2 Proportion of magnesium phosphate cement-based materials described in Comparative Examples 1 to 5 (kg / m 3 )
[0140]
[0141] According to the above specifications, setting time, compressive strength, flexural strength and tensile strength tests were performed on Examples 1 to 8 and Comparative Examples 1 to 5, respectively. The test results are shown in Table 3.
[0142] Table 3 Coagulation time and mechanical properties of Examples 1 to 8 and Comparative Examples 1 to 5
[0143]
[0144] As can be seen from Table 3, the 3 h compressive strength of Examples 1 to 4 of the present invention is between 75 and 92 MPa, the 3 h flexural strength is between 32 and 37 MPa, and the 3 h tensile strength is between 7 and 10 MPa. Among them, the measured 3 h flexural strength has fully met the 28 d flexural strength requirements specified in RPC180 grade (GB / T 31387-2015) (i.e. ≥ 24 MPa); the 3 h highest direct tensile strength has met the tensile strength requirements specified in UT4 (T / CECS 10107-2020) (i.e. ≥ 10 MPa); in addition, in Example 4, although the setting time of the material is extended to 35 min, its 3 h compressive strength is still as high as 75 MPa, which is significantly higher than the requirement for the 28 d compressive strength of ultra-early strength magnesium phosphate repair mortar in JC / T2537-2019 (i.e. ≥ 45 MPa). In addition, the 1-day compressive strength of all examples has met the requirements of RPC100 grade (GB / T 31387-2015) for 28-day compressive strength (i.e., ≥100 MPa), and the 7-day compressive strength of Examples 1 and 3 has met the requirements of RPC120 grade (GB / T 31387-2015) for 28-day compressive strength (i.e., ≥120 MPa). It can be seen that compared with the ultra-high performance cement-based material (concrete) of silicate cement, the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material of the present invention has significantly higher (ultra) early mechanical properties, which can meet the engineering needs of different fields, especially the above-mentioned maintenance / reinforcement, emergency repair, emergency construction projects with special requirements for early-age strength, and emergency safety consolidation of nuclear waste.
[0145] By comparison with Comparative Example 1, it can be seen that when the auxiliary cementitious material (wollastonite powder, metakaolin, fly ash) adopted by the present invention is not used to achieve the closest packing of different active combinations and particles, the 3 h flexural strength in Comparative Example 1 is only 20 MPa, and the 3 h direct tensile strength is only 4 MPa, which are significantly lower than the corresponding 3 h strength values of Examples 1 to 4; in addition, although its 3 h compressive strength is 82 MPa, its 28 d compressive strength is only 103 MPa, which is still lower than the 28 d compressive strength requirement of RPC 120 grade (GB / T31387-2015) (i.e. ≥ 120 MPa), and its setting time is only 16 min, which is not conducive to construction (preparation) operation.
[0146] By comparison with Comparative Example 2, it can be seen that when the Mg / PO4 molar ratio is 4, although the setting time of Comparative Example 2 is extended, its mechanical properties are significantly reduced compared with those of Example 1, especially the early strength, such as the 3 h compressive strength is only 28 MPa. It can be seen that the Mg / PO4 molar ratio range of the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material of the present invention is scientifically reasonable; at the same time, it also proves the excellent mechanical properties of the material of the present invention.
[0147] By comparison with Comparative Example 3, it can be seen that when ultrafine fly ash, which also plays a "water-reducing" role, is used alone, the reduction in the water-cement ratio of Comparative Example 3 is much lower than the water-cement ratio of the composite use of silica fume and ultrafine fly ash in Example 3 and the water-cement ratio of the silica fume alone in Example 5, and the setting time is reduced by 5 min and 12 min compared with Examples 3 and 5, respectively. Although the 3 h compressive strength of Comparative Example 3 exceeds 70 MPa, its compressive strength at 28 days is still lower than 100 MPa, which does not meet the compressive strength requirements of UHPC, and is much lower than Examples 3 and 5. This proves the significant effectiveness of the method of using silica fume as the basic cementitious material and the composite use of silica fume and ultrafine fly ash in the material of the present invention to improve the comprehensive performance of the material.
[0148] By comparison with Comparative Examples 4 and 5, it can be seen that when boric acid and zinc acetate are used alone, the setting time of Comparative Examples 4 and 5 is only no more than 5 min, and even insufficient time is provided for preparing the material, while the setting time of Example 1 having the same parameters is 22 min, which can ensure the preparation and use time of the material. This shows that the composite retarder used in the present invention effectively solves the problem that potassium magnesium phosphate cement cannot be used due to too fast setting time at ultra-low water-cement ratio, and is the basis for preparing ultra-early strength ultra-high performance potassium magnesium phosphate cement-based composite materials.
[0149] By comparing Examples 1 and 2 with Example 5, it can be seen that the composite use of silica fume, wollastonite powder and metakaolin in the present invention can improve its early mechanical properties, including compressive, flexural and tensile strength, compared with the use of silica fume alone, especially the early flexural and tensile performances are improved to a high extent, and Examples 1 and 2 respectively improve the 3 h tensile strength by 45% and 23% and the 3 h flexural strength by 28% and 35% compared with Example 3. This shows that the composite effect of wollastonite powder, metakaolin and silica fume has a significant effect on improving the performance of the material of the present invention.
[0150] In addition, relative to Example 1, when silica fume is not added and all wollastonite powder is added at the dosage of silica fume and wollastonite powder, the fluidity is too low and molding cannot be performed at the same water-binder ratio. Relative to Example 2, when silica fume is not added and all kaolin is added at the dosage of silica fume and kaolin, the fluidity is too low and molding cannot be performed at the same water-binder ratio. Relative to Example 3, when silica fume is not added and all ultrafine fly ash is added at the dosage of silica fume and ultrafine fly ash, molding cannot be performed at the same water-binder ratio because the fluidity is too low.
[0151] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. An ultra-early-strength and ultra-high-performance potassium magnesium phosphate cement-based composite material, characterized in that: The dosage ratio of each component of the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material is as follows: Dead-burned magnesium oxide 767.6~900 kg / m 3 ; Potassium dihydrogen phosphate 300~432.0 kg / m 3 ; Silica fume 151~302 kg / m 3 ; Auxiliary cementitious materials 0~200kg / m 3 ; Sodium dihydrogen phosphate 0~100 kg / m 3 ; Quartz sand 400~1000 kg / m 3 ; Composite retarder 13.2~26.4 kg / m 3 ; Water reducing agent 0.7~7 kg / m 3 ; Fiber 100~240 kg / m 3 ; Water 180~226 kg / m 3 ; The ratio of water to potassium dihydrogen phosphate is 0.53 to 0.66, and the molar ratio of magnesium to phosphorus is 7 to 8; The composite retarder is a mixture of zinc acetate and boric acid, or a mixture of zinc acetate and sodium borate, or a mixture of zinc acetate, boric acid and sodium borate; The water-to-binder ratio is 0.14-0.15; The water reducer is a naphthalene-based water reducer; The auxiliary cementitious material is selected from one or more of fly ash, wollastonite powder and metakaolin.
2. The ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material according to claim 1, characterized in that: The dead-burned magnesium oxide has an average particle size of 20 to 60 μm, and the dead-burned magnesium oxide includes MgO, and the MgO content is ≥85%; The potassium dihydrogen phosphate has an average particle size of 50 to 300 μm and a purity of ≥90%; The average particle size of the silica fume is 0.1-0.3 μm, and the silica fume includes SiO2, and the SiO2 content is ≥90%; The quartz sand particle size is 0.16-1.25 mm.
3. The ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material according to claim 1, characterized in that: The average particle size of the wollastonite powder is 10-23 μm, the average particle size of the metakaolin is 2-10 μm, and the average particle size of the fly ash is 5-25 μm.
4. The ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material according to claim 1, characterized in that: The average particle size of the sodium dihydrogen phosphate is 50-600 μm, and the purity is ≥90%.
5. The ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material according to claim 1, characterized in that: The zinc acetate is zinc acetate dihydrate.
6. The ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material according to claim 1, characterized in that: The solid mixture is dead-burned magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, silica fume, auxiliary cementitious material, quartz sand and water reducing agent; The method for using the composite retarder is selected from one or more of the following methods: Method 1: dissolving the composite retarder in mixing water, and then mixing to prepare the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material; Method 2: dissolving zinc acetate in the composite retarder in mixing water, adding boric acid and / or sodium borate into the solid mixture, and then mixing to prepare the ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material; Method 3: Add the composite retarder into the solid mixture, and then add water to mix to prepare an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material.
7. The ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material according to claim 1, characterized in that: The fibers include steel fibers or composite fibers including steel fibers and non-metallic fibers. The steel fibers are fine steel fibers with a diameter of 0.1 to 0.22 mm and a length of 6 to 20 mm. The steel fibers include one or more of copper-plated steel fibers, stainless steel fibers, and ordinary carbon steel fibers. The non-metallic fibers include one or more of POM fibers, PE fibers, PVA fibers, and PP fibers.
8. A method for preparing an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material according to any one of claims 1 to 7, characterized in that: The following steps are included: Mix water, dead-burned magnesium oxide, potassium dihydrogen phosphate, sodium dihydrogen phosphate, silica fume, auxiliary cementitious material, quartz sand, water reducing agent and composite retarder, stir until slurry is formed, then add steel fiber or steel fiber and other non-metallic fiber composite and stir rapidly to make the fiber evenly dispersed in the slurry to obtain a mixture; The prepared mixture is formed in a mold or directly applied to actual engineering projects, and the mixture forms an ultra-early strength and ultra-high performance potassium magnesium phosphate cement-based composite material after solidification and hardening.
Citation Information
Patent Citations
An ultra-high performance repair concrete based on a sulfoaluminate-silicate cement system
CN110803906B
A preparation process for modified cement and its early-strength ultra-high performance concrete
CN115784647B
Ultra-high performance concrete with ultra-high early strength and preparation method thereof
CN115819052A
High-bending-resistance super-early-strength UHPC with initial setting time longer than 30 min and preparation method of high-bending-resistance super-early-strength UHPC
CN116813283A
Water-resisting potassium phosphate magnesium cement and preparation method thereof
CN104310831A